A Gendered Perspective on Human Trafficking Perpetrators: Evidence from Russia. Issue 1 (1st January 2020) - McCarthy, Lauren A.
ABSTRACT: The dominant depiction of human trafficking is that of a violent man trafficking an innocent, subordinate female victim for sexual exploitation. However, this does not represent the diversity of the experience of human trafficking. Increasingly, research has suggested that women are also perpetrators of human trafficking and that men and boys are frequently victims. Using a content analysis of Russian media articles on trafficking cases from 2003 to 2013, I examine women perpetrators of trafficking. I show that women have leveraged gender stereotypes and their positions in society to participate in trafficking in a variety of ways and that they are also enabled by particular structural characteristics of the trafficking business. I argue that a gendered perspective on perpetrators combined with deep empirical analysis can help us better understand what trafficking looks like in reality and how the experiences of women in trafficking are more complex than stereotypes would have us believe.